A compact six port antenna for better spectrum utilization efficiency in cognitive radio applications. Issue 10 (6th August 2020) - Srikar, D.; Anuradha, Sundru
Abstract: In this article, a novel six port antenna for better spectrum utilization efficiency in cognitive radio (CR) applications is presented. In this six port antenna system, an ultra‐wideband (UWB) sensing antenna and five wideband/narrowband (NB) antennas are integrated on the same substrate in a compact area of 1134 mm 2 . Antenna associated with port 1, which is meant for sensing, has −10 dB reflection coefficient bandwidth of 3 to 11 GHz and the antennas associated with ports 2, 3, 4, 5, and 6 have −10 dB reflection coefficient bandwidths of 3.6 to 5.8 GHz (single band), 2.9 to 3.6 GHz and 5.4 to 7.98 GHz (dual band), 7.95 to 8.38 GHz and 9 to 9.85 GHz (dual band), 8.38 to 9 GHz (single band) and 9.7 to 10.7 GHz (single band), respectively. Minimum isolation of 20 dB is attained between UWB sensing antenna and any narrowband/wideband antenna except between the antennas associated with ports 1 and 2 where minimum isolation of 12 dB is achieved over the operating bandwidth of UWB sensing antenna. Moreover, among all wideband/narrowband antennas, isolation of less than 15 dB is achieved. More importantly, the narrowband and wideband antennas meant for communication cover all frequency bands in UWB and a good match between the simulated and measured results is noticed.